Empowering Communities To Outsmart Stroke: Strengthening Coping Skills Through The Cerdik Movement And Cadre Leadership - Tri Wahyuni Ismoyowati; Hana Priscilla Frudence Sohilait (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Stroke is a leading cause of disability and death among the elderly. Risk factors such as hypertension, diabetes, high cholesterol, and chronic stress are often not optimally managed due to a lack of knowledge and adaptive coping strategies among the elderly and their families. This community service activity aimed to enhance the coping management capacity of the elderly and their families in dealing with stroke risk factors through an educational approach based on the CERDIK program (Regular health check-ups, Eliminate smoking, Routine physical activity, Balanced diet and nutrition, Adequate rest, and Stress management). The implementation methods included situation analysis, interactive counseling, coping skills training, mentoring, and pre- and post-intervention evaluation. The results showed a significant improvement in knowledge, health behavior changes, and adaptive coping abilities among the elderly and their families. This intervention proved effective in a community setting and is considered feasible for replication as a primary stroke prevention effort. The community service outcomes revealed that prior to the education, most community members had a moderate level of stroke prevention awareness (46.7%), and some had poor prevention practices. After the educational intervention, there was a notable increase, with the majority demonstrating good prevention practices (60%) and none remaining in the poor category. Post-intervention, a significant increase in stroke prevention awareness and understanding of the CERDIK principles was observed among participants. This intervention is recommended for integration into Puskesmas (community health center) and elderly Posyandu (integrated health posts) programs..